Experimental Study on Stress Wave Propagation Crossing the Jointed Specimen with Different JRCs - S.N. Hong (Hindawi Limited, 2021)
Most of the rock masses in the outer crust of the Earth are discontinuous. They are divided by joints, faults, fractures, etc. And those discontinuities, generally referred to as joints, greatly affect the property of the rock masses. The paper experimentally investigates the stress wave propagation crossing the jointed specimens. The tests were conducted on the split Hopkinson pressure bar (SHPB). The test specimens consist of two parts cast by cement mortar. Both parts have an irregular surface, and they were designed to match each other completely. The surfaces where two parts meet make an artificial joint. The surfaces of the joints were scanned by a three-dimensional scanner to obtain its actual topography and then to calculate the roughness of the surface, i.e., the joint roughness coefficient (JRC). A set of jointed specimens with JRC ranging from 0 to 20 were made and used in dynamic compression experiments. During the tests, signals were captured by strain gauges stuck on the incident and transmitted bars of the SHPB apparatus. The incident, reflected, and transmitted waves across the jointed specimens were obtained from the test records. We found out that more stress wave would transmit through the jointed specimen with larger JRC. Besides, collected data were processed to get the dynamic stress-strain relation of jointed specimens and the stress-closure curves of the joints. The results show that the joint increases the deformation of the specimen, and the stiffness of the jointed specimen would increase slightly when the joint is rougher.